School of fear - class is not dismissed! - Daneshvari, Gitty (Atom, 2012)
Thirteen year olds Madeleine, Theo, and Lulu, fourteen year old Garrison, and ten year old new "contestant" Hyacinth, must face their phobias and join forces to learn who is stealing wigs and pageant trophies from the School of Fear
Ist Bd. 2 einer ungezählten Serie
Keywords: Phobias / Juvenile fiction; Schools / Juvenile fiction; Interpersonal relations / Juvenile fiction; Self-actualization (Psychology) / Juvenile fiction; Brigands and robbers / Juvenile fiction; Children's stories; Massachusetts / Juvenile fiction